Eco-Friendly Keratin-Based Additives in the Polymer Matrix to Enhance the Output of Triboelectric Nanogenerators - Joo, Seokwon; Kim, Jong Hyeok; Lee, Chae Eun; Kang, Jeongmin; Seo, Soonmin; Kim, Ju Hyung; Song, Yoon Kyu (ACS Applied Bio Materials, 2022)
A triboelectric nanogenerator (TENG) is an energy generator that converts mechanical energy into electrical energy using triboelectricity at a nanoscale. Given their potential application as power sources in electronic devices, various attempts have been made to improve their output performance. Here, we present an eco-friendly, low-cost, and facile fabrication method to enhance TENG characteristics with keratin protein additives. Keratin sources, human and cat hair, are processed into powder and added to the friction layer, which increases their positive charge affinity, thereby boosting the output performance of the TENG. The output performances of the keratin-added TENG (K-TENG) are measured in the vertical contact-separation mode, with both additives having the highest output values at 5 wt % load. The K-TENG generates more output voltage and current values than the pristine TENG by 90 and 208%, respectively. Hence, we conclude that this method would potentially promote TENG as a strong candidate for a competitive "green" energy harvesting device in future electronics applications. copy; 2022 American Chemical Society.
Keywords: Eco-friendly; Eco-friendly energy harvester; Energy; Energy Harvester; Hair; Nanogenerators; Output performance; Polymer composite; Polymer matrices; Triboelectric nanogenerator; Cytoskeleton; Electric Power Supplies; Electronics; Humans; Keratins; Polymers; additives; eco-friendly energy harvesters; hairs; keratin; polymer composites; triboelectric nanogenerators